Ethical challenges in designing and implementing health systems research: Experiences from the field. Issue 3 (2nd July 2016) - Hyder, Adnan; Krubiner, Carleigh
ABSTRACT: Background: Health systems research (HSR) seeks to generate knowledge to improve the mechanisms for delivering quality health services and improving population health outcomes. HSR covers a wide range of research questions, including health financing, service delivery, human resources for health, and quality improvement. Because HSR has its own definitions, methods, and analytic approaches, there is an increasing realization that these studies may raise ethical concerns that differ from other types of research. Despite the increasing interest and investment in HSR over the past several years, there is little empirical research examining the kinds of ethical challenges that arise in the design and implementation of these studies. A deeper understanding of the kinds of ethical issues encountered in various types of HSR could help researchers prepare for these challenges and better inform ethical review processes.Methods: Using semistructured qualitative interviews with 16 researchers involved in the Future Health Systems Consortium and Johns Hopkins–Fogarty African Bioethics Consortium, we conducted an exploratory study to identify some common or poignant ethical challenges in HSR.Results: Thematic analysis of interview transcripts using an inductive approach revealed ethics issues in HSR surrounding the following topics: privacy and confidentiality, associated harms, appropriate consent, institutional review board (IRB) review, appropriate controls, research ownership and control, responsiveness, posttrial issues, sustainability, and collaboration and competition.Conclusions: Though not exhaustive, this preliminary account highlights the nuanced and unique ethical challenges that can arise in HSR and underscores the need for different kinds of ethical guidance and oversight for HSR studies.